2017
DOI: 10.1109/jestpe.2017.2714026
|View full text |Cite
|
Sign up to set email alerts
|

Stability Assessment of Power-Converter-Based AC systems by LTP Theory: Eigenvalue Analysis and Harmonic Impedance Estimation

Abstract: Abstract-Stability analysis of power-converter-based AC systems poses serious challenges not only because of the non-linear nature of power converters, but also because linearisation is not generally applied around a steady-state operating point, as in the DC case, but around a time-periodic operating trajectory. Typical examples are single-phase and unbalanced three-phase systems. In this paper, two general methods to assess stability of the aforementioned systems are presented. Both are based on the Linear T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 29 publications
0
50
0
1
Order By: Relevance
“…The wide frequency range of oscillations are tightly coupled with the electric network dynamics, leading to a very high-order system state matrix [67], which consequently imposes a high computational burden for the stability analysis. Moreover, in order to capture the frequency-coupling dynamics of unbalanced threephase power systems, the HSS models of ac-dc converters are required, which also complicates the model derivation process with the increased system order [68].…”
Section: A Eigenvalue Analysismentioning
confidence: 99%
“…The wide frequency range of oscillations are tightly coupled with the electric network dynamics, leading to a very high-order system state matrix [67], which consequently imposes a high computational burden for the stability analysis. Moreover, in order to capture the frequency-coupling dynamics of unbalanced threephase power systems, the HSS models of ac-dc converters are required, which also complicates the model derivation process with the increased system order [68].…”
Section: A Eigenvalue Analysismentioning
confidence: 99%
“…Hence, two new state equations are added to the controller model in (30) and (31), where according to the control scheme shown in Fig. 5…”
Section: B Pq Controller Modelmentioning
confidence: 99%
“…A comprehensive review of the basics of LTP theory is reported in [31], [32], and only a brief summary is given here, mainly to clarify the notation. Once the steady-state operating conditions have been found from the NLTP system (7), the stability may be determined by linearising the NLTP system around the steady-state periodic operating trajectory [33], [34], which gives an LTP system on which the stability analysis is performed.…”
Section: Basic Theory For the Stability Analysis Of Ltp Systemsmentioning
confidence: 99%